Simultaneous mass spectrometry analysis of cisplatin with oligonucleotide-peptide mixtures: implications for the mechanism of action - Mansouri, Farangis (2022)
Although genomic DNA is the primary target of anticancer platinum-based drugs, interactions with proteins also play a significant role in their overall activity. In this study, competitive binding of cisplatin with an oligonucleotide and two peptides corresponding to segments of H2A and H2B histone proteins was investigated by mass spectrometry. Following the determination of the cisplatin binding sites on the oligonucleotide and peptides by tandem mass spectrometry, competitive binding was studied and transfer of platinum fragments from the platinated peptides to the oligonucleotide explored. In conjunction with previous studies on the nucleosome, the results suggest that all four of the abundant histone proteins serve as a platinum drug reservoir in the cell nucleus, providing an adduct pool that can be ultimately transferred to the DNA.